Thinking Back about a Positive Event: The Impact of Processing Style on Positive Affect - Nelis, Sabine; Holmes, Emily A.; Palmieri, Rosa; Bellelli, Guglielmo; Raes, Filip (Frontiers in Psychiatry, 2015)
The manner in which individuals recall an autobiographical positive life event has affective consequences. Two studies addressed the processing styles during positive memory recall in a non-clinical sample. Participants retrieved a positive memory which was self-generated (Study 1, n = 70) or experimenter-chosen (i.e., academic achievement, Study 2, n = 159), followed by the induction of one of three processing styles (between-subjects): In Study 1, a ‘concrete/imagery’ vs. ‘abstract/verbal’ processing style was compared. In Study 2, a ‘concrete/imagery’, ‘abstract/verbal’, and ‘comparative/verbal’ processing style were compared. The processing of a personal memory in a concrete/imagery-based way led to a larger increase in positive affect compared to abstract/verbal processing in Study 1, as well as compared to comparative/verbal thinking in Study 2. Results of Study 2 further suggest that it is making unfavourable verbal comparisons that may hinder affective benefits to positive memories (rather then general abstract/verbal processing per se). The comparative/verbal thinking style failed to lead to improvements in positive affect, and with increasing levels of depressive symptoms it had a more negative impact on change in positive affect. We found no evidence that participant’s tendency to have dampening thoughts in response to positive affect in daily life contributed to the affective impact of positive memory recall. The results support the potential for current trainings in boosting positive memories and mental imagery, and underline the search for parameters that determine at times deleterious outcomes of abstract/verbal memory processing in the face of positive information.